Effects of aerobic exercises on fasting blood glucose and blood pressure in patients with Type 2 diabetes living with hypertension in Ghana - Mshunqane, Nombeko (University of Pretoria, 2022)
Dissertation (MSc (Physiotherapy))--University of Pretoria, 2021.